The restoration of the Sistine Chapel (Edizioni Musei Vaticani, 1994)
Gianluigi Colalucci, master restorer, and Carlo Pietrangeli, director-general of the Pontificial Academy of Science, recount their experiences in restoring Michelangelo's frescos in the Sistine Chapel.